2005
DOI: 10.1590/s1413-70542005000100018
|View full text |Cite
|
Sign up to set email alerts
|

Adaptabilidade de caprinos exóticos e naturalizados ao clima semi-árido do nordeste brasileiro

Abstract: RESUMORealizou-se este estudo com dezesseis caprinos machos, sendo oito exóticos (4 da raça Boer e 4 da Anglo-Nubiana) e oito naturalizados (4 da raça Moxotó e 4 da Pardo-Sertaneja), todos puros e com idade de um ano. Os animais tiveram a temperatura retal, freqüência respiratória, freqüência cardíaca, temperatura da fronte, das costelas, do flanco e do escroto, mensuradas pela manhã e à tarde, no período de 21 de agosto a 04 de Setembro de 2002, e foram submetidos a um teste de tolerância ao calor no período … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
36

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 6 publications
4
7
0
36
Order By: Relevance
“…Even under high environmental status, the confined animal and semi-TR remained confined within the normal range, which according to REECE (1996) should be between 38.5 and 39.7 ºC. The results found in this study are similar to those found by SANTOS et al (2005), who observed that the Moxotó goats had TR at 39.2 ºC in the morning, in a state of comfort, and afternoon TR at 40.16 ºC in a situation of heat stress.…”
Section: Resultssupporting
confidence: 87%
“…Even under high environmental status, the confined animal and semi-TR remained confined within the normal range, which according to REECE (1996) should be between 38.5 and 39.7 ºC. The results found in this study are similar to those found by SANTOS et al (2005), who observed that the Moxotó goats had TR at 39.2 ºC in the morning, in a state of comfort, and afternoon TR at 40.16 ºC in a situation of heat stress.…”
Section: Resultssupporting
confidence: 87%
“…Os dados registrados apresentam-se inferiores aos registrados por Santos et al (2005), em estudos de avaliação da adaptabilidade de caprinos na região Semi-árida, cujas médias obtidas para o ITGU foram: 77,5 e 85,5 na sombra, para os turnos da manhã e tarde respectivamente e de 98 à tarde em ambiente de sol.…”
Section: Resultsunclassified
“…Com relação ao turno, as médias da tarde foram maiores que as da manhã. Resultados semelhantes aos observados por Santos et al (2005) para as raças puras: Boer, Anglo-Nubiana, Moxotó e Pardo-Sertaneja. Essa variação ocorreu provavelmente em função do menor gradiente térmico entre a superfície dos animais e a temperatura do ar, no turno da tarde por causa da elevação da temperatura do ar, conforme Tabela 3.…”
Section: Temperatura Superficialunclassified
See 1 more Smart Citation
“…Between the breeds, the preference for water exposed to the sun was the Azul (71.18%), followed by Moxotó (65.95%) and Graúna (57%). This preference for the water exposed to the sun can be explained by the adaptation that native goats had throughout its evolution in semiarid northeastern region (SANTOS et al, 2005;and SILVA et al, 2010), where the temperature is always high, which also raises the temperature of the water, but also highlights the need to establish values of ideal water temperature for goats, especially those bred in arid and semiarid regions, mainly due to the small amount of information available on these animals in these regions (ARAÚJO et al, 2010). ROCHA et al (2009), comparing the adaptation of Saanen and Azul goats in the Mid North region of Brazil, during the rainy and dry season, concluded that the Azul breed was more adapted to the experimental conditions.…”
Section: Shade Watermentioning
confidence: 99%